Evaluation of the biochemical and physiological activity of the natural compound, 2,4-ditert-butylphenol on weeds - T. S. Chuah; M. Z. Norhafizah; B. S. Ismail (2015)
2,4-Di-tert-butylphenol (2,4-DTBP) is a natural compounds present in medicinal plants. It is reported to have herbicidal properties. However, the mechanism of action is unknown for use in weed management. Measurements were made of lipid peroxidation, ion leakage, antioxidant enzymes, chlorophyll content, chlorophyll fluorescence and photosynthesis in the grassy weed Leptochloa chinensis (L.) Nees and the broadleaf weed Hedyotis verticillata (L.) Lam. at 7 and 14 days, respectively, after treatment with 2,4-DTBP. The 2,4-DTBP reduced the shoot fresh weight of L. chinensis and H. verticillata by 50% when applied at concentrations of 50 and 200 µg mL–1, respectively. Treatment with 2,4-DTBP significantly increased levels of malondialdehyde, caused excessive ion leakage and increased activities of antioxidant enzymes such as superoxide dismutase, peroxidase and catalase in leaf and root tissues of the two bioassay species. Most notably, 2,4-DTBP treatment caused great reduction in chlorophyll content, thereby decreasing chlorophyll fluorescence, transpiration and net photosynthetic rate in the leaf tissues. The results suggest that 2,4-DTBP induces oxidative stress through the generation of reactive oxygen species, which cause lipid peroxidation and membrane damage in root tissues and chloroplast in leaf tissues, thus leading to increased levels of antioxidant enzymes.